Characterizing heatwaves based on land surface energy budget - Yinglin Tian; Axel Kleidon; Corey Lesk; Sha Zhou; Xiangzhong Luo; Sarosh Alam Ghausi; Guangqian Wang; Deyu Zhong; Jakob Zscheischler (Communications Earth & Environment, 2024)
Abstract Heat extremes pose pronounced threats to social-ecological systems and are projected to become more intense, frequent, and longer. However, the mechanisms driving heatwaves vary across heatwave types and are not yet fully understood. Here we decompose perturbations in the surface energy budget to categorize global heatwave-days into four distinct types: sunny–humid (38%), sunny-dry (26%), advective (18%), and adiabatic (18%). Notably, sunny-dry heatwave-days decrease net ecosystem carbon uptake by 0.09 gC m−2 day−1 over harvested areas, while advective heatwave-days increase the thermal stress index by 6.20 K in populated regions. In addition, from 2000 to 2020, sunny-dry heatwaves have shown the most widespread increase compared to 1979 to 1999, with 67% of terrestrial areas experiencing a doubling in their occurrence. Our findings highlight the importance of classifying heatwave-days based on their underlying mechanisms, as this can enhance our understanding of heatwaves and improve strategies for heat adaptation.